2022
DOI: 10.1038/s41598-022-23573-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MR fingerprinting with a short acquisition window in consecutive patients referred for clinical CMR and healthy volunteers

Abstract: Cardiac Magnetic Resonance Fingerprinting (cMRF) has been demonstrated to enable robust and accurate T1 and T2 mapping for the detection of myocardial fibrosis and edema. However, the relatively long acquisition window (250 ms) used in previous cMRF studies might leave it vulnerable to motion artifacts in patients with high heart rates. The goal of this study was therefore to compare cMRF with a short acquisition window (154 ms) and low-rank reconstruction to routine cardiac T1 and T2 mapping at 1.5 T. Phantom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Another prevalent approach in MRF sequence design involves incorporating magnetization preparation modules dedicated to enhancing tissue property encoding in the signal rather than for image acquisition, such as the diffusion preparation in mdMRF scans. This strategy proves especially valuable in scenarios like breast MRF 41 and cardiac MRF, 8,42 where signal sensitivity to tissue properties is low because of short acquisition windows. The three example MRF applications presented here illustrate a variety of MRF sequence architectures, each accompanied by a prototype optimizer.…”
Section: Discussionmentioning
confidence: 99%
“…Another prevalent approach in MRF sequence design involves incorporating magnetization preparation modules dedicated to enhancing tissue property encoding in the signal rather than for image acquisition, such as the diffusion preparation in mdMRF scans. This strategy proves especially valuable in scenarios like breast MRF 41 and cardiac MRF, 8,42 where signal sensitivity to tissue properties is low because of short acquisition windows. The three example MRF applications presented here illustrate a variety of MRF sequence architectures, each accompanied by a prototype optimizer.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes several studies that have validated various cardiac MRF techniques against conventional cardiac mapping techniques 147,148,153–159,162,163 . Generally, although absolute T1 and T2 values differ between MRF-derived mapping and conventional mapping, there is good correlation between MRF and conventional mapping sequences in all studies.…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
“…The long acquisition window in cMRF makes it particularly vulnerable to artifacts in the case of a subject with a high heart rate. In [105], the authors demonstrated that cMRF The long acquisition window in cMRF makes it particularly vulnerable to artifacts in the case of a subject with a high heart rate. In [105], the authors demonstrated that cMRF is less precise than conventional quantitative MRI acquisitions especially for subjects with high heart rates.…”
Section: Cardiac Imagingmentioning
confidence: 99%
“…In [105], the authors demonstrated that cMRF The long acquisition window in cMRF makes it particularly vulnerable to artifacts in the case of a subject with a high heart rate. In [105], the authors demonstrated that cMRF is less precise than conventional quantitative MRI acquisitions especially for subjects with high heart rates. The advantage of cMRF is that it allows for higher-resolution acquisition.…”
Section: Cardiac Imagingmentioning
confidence: 99%